Letter from C.M. Potter to James Curtis Booth - Potter, C. M. (1887)
C.M. Potter writes James Curtis Booth (1810-1888) a thank-you note for a donation made to the Hobart College Library.
Keywords: Booth, James Curtis, 1810-1888; Charity; Hobart College